Swooning, stereotypes, and observing a birth—the Sharp Scratch roundup. (5th August 2021) - MacFarlane, Andrew; Phillips, Callum; Oki, Olukayode; Harvey, Anna; Nabavi, Nikki
Abstract : Highlights from the Sharp Scratch podcast series